What is the state of children's participation in qualitative research on health interventions?: a scoping study - Jean M. Hunleth; Julie S. Spray; Corey Meehan; Colleen Walsh Lang; Janet Njelesani (BMC, 2022)
Abstract Background Children are the focus of numerous health interventions throughout the world, yet the extent of children's meaningful participation in research that informs the adaptation, implementation, and evaluation of health interventions is not known. We examine the type, extent, and meaningfulness of children's participation in research in qualitative health intervention research. Method A scoping study was conducted of qualitative published research with children (ages 6-11 years) carried out as part of health intervention research. Following Arksey and O'Malley's scoping study methodology and aligned with the PRISMA-ScR guidelines on the reporting of scoping reviews, the authors searched, charted, collated, and summarized the data, and used descriptive and content analysis techniques. Ovid MEDLINE was searched from 1 January 2007 to 2 July 2018 using the keywords children, health intervention, participation, and qualitative research. Study selection and data extraction were carried out by two reviewers independently. Results Of 14,799 articles screened, 114 met inclusion criteria and were included. The study identified trends in when children were engaged in research (e.g., post-implementation rather than pre-implementation), in topical (e.g., focus on lifestyle interventions to prevent adult disease) and geographical (e.g., high-income countries) focuses, and in qualitative methods used (e.g., focus group). While 78 studies demonstrated meaningful engagement of children according to our criteria, there were substantial reporting gaps and there was an emphasis on older age (rather than experience) as a marker of capability and expertise. Conclusions Despite evidence of children's meaningful participation, topical, geographical, and methodological gaps were identified, as was the need to strengthen researchers' skills in interpreting and representing children's perspectives and experiences. Based on these findings, the authors present a summary reflective guide to support researchers toward more meaningful child participation in intervention research.